Knowledge management orientation: An innovative perspective to hospital management - Ghasemi, Matina; Nejad, Mazyar Ghadiri; Bagzibagli, Kemal (Iranian Journal of Public Health, 2017)
Background: By considering innovation as a new project in hospitals, all the project management’s standard steps should be followed in execution. This study investigated the validation of a new set of measures in terms of providing a procedure for knowledge management-oriented innovation that enriches the hospital management system. Methods: The relation between innovation and all the knowledge management areas, as the main constructs of project management, was illustrated by referring to project management standard steps and previous studies. Through consultations and meetings with a committee of professional project managers, a questionnaire was developed to measure ten knowledge management areas in hospital’s innovation process. Additionally, a group of experts from hospital managers were invited to comment on the applicability of the questionnaires by considering if the items are measurable in hospitals practically. Results: A close-ended, Likert-type scale items, consisted of ten sections, were developed based on project management body of knowledge thorough Delphi technique. It enables the managers to evaluate hospitals’ situation to be aware whether the organization follows the knowledge management standards in innovation process or not. By pilot study, confirmatory factor analysis and exploratory factor analysis were conducted to ensure the validity and reli-ability of the measurement items. Conclusion: The developed items seem to have a potential to help hospital managers and subsequently delivering new products/services successfully based on the standard procedures in their organization. In all innovation processes, the knowledge management areas and their standard steps help hospital managers by a new tool as questionnaire format. © 2017, Iranian Journal of Public Health. All rights reserved.
Keywords: Hospital management; Innovation; Knowledge management area